Pengaruh Bauran Pemasaran Terhadap Kepuasan Konsumen Dan Word Of Mouth Studi Kasus Terhadap Lip Tint Wardah - Nabilah Sugiarto; Indra Rizky Kurnia Hutabarat; Andhyka Tyaz Nugraha (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to analyze the influence of the marketing mix on satisfaction of consumer and positive Word of Mouth (WOM), with consumer satisfaction serving as a mediating variable. The primary problem addressed is the increasing competition in the halal cosmetics market and the crucial role of credible WOM as a Promotional tool. The research uses method which is a quantitative approach as well as Structural Equation Modeling-Partial Least Square (SEM-PLS) and involves 126 female respondents who are users of Wardah's Liptint.The results show that the marketing mix has a significant and positive influence on both consumer satisfaction (?=0.889) and WOM (?=0.662). Consumer satisfaction is identified as a vital mediator, indicating that the marketing mix indirectly affects WOM through increased consumer satisfaction. This finding concludes that an optimal marketing mix strategy is essential for enhancing consumer satisfaction and fostering positive WOM, which in turn strengthens Wardah's position in the market.